Multifunctional Protein A Is the Only Viral Protein Required for Nodavirus RNA Replication Crown Formation - Johan A. den Boon; Hong Zhan; Nuruddin Unchwaniwala; Mark Horswill; Kailey Slavik; Janice Pennington; Amanda Navine; Paul Ahlquist (Viruses, 2022)
Positive-strand RNA virus RNA genome replication occurs in membrane-associated RNA replication complexes (RCs). Nodavirus RCs are outer mitochondrial membrane invaginations whose necked openings to the cytosol are “crowned” by a 12-fold symmetrical proteinaceous ring that functions as the main engine of RNA replication. Similar protein crowns recently visualized at the openings of alphavirus and coronavirus RCs highlight their broad conservation and functional importance. Using cryo-EM tomography, we earlier showed that the major nodavirus crown constituent is viral protein A, whose polymerase, RNA capping, membrane interaction and multimerization domains drive RC formation and function. Other viral proteins are strong candidates for unassigned EM density in the crown. RNA-binding RNAi inhibitor protein B2 co-immunoprecipitates with protein A and could form crown subdomains that protect nascent viral RNA and dsRNA templates. Capsid protein may interact with the crown since nodavirus virion assembly has spatial and other links to RNA replication. Using cryoelectron tomography and complementary approaches, we show that, even when formed in mammalian cells, nodavirus RC crowns generated without B2 and capsid proteins are functional and structurally indistinguishable from mature crowns in infected Drosophila cells expressing all viral proteins. Thus, the only nodaviral factors essential to form functional RCs and crowns are RNA replication protein A and an RNA template. We also resolve apparent conflicts in prior results on B2 localization in infected cells, revealing at least two distinguishable pools of B2. The results have significant implications for crown structure, assembly, function and control as an antiviral target.